Odpowiedzi

Najlepsza Odpowiedź!
2010-03-15T22:37:25+01:00
A) (a+b)-(2a-b)-(a-2b) =
a+b-2a+b-a+2b=
-2a+4b

b) (3x-y+1)-(x+y)+(y-x) =
3x-y+1-x-y+y-x=
x-y+1

c)- (kx+ny)-(3kx+2ny)+(5kx-3ny) =
-kx-ny-3kx-2ny+5kx-3ny=
kx-6ny

d) (2ab+a+3)-(3ab-a+3) =
2ab+a+3-3ab+a-3=
-ab+2a

e) (4x²-3x)-(x+0,1x²)-(x²-0,1x) =
4x²-3x-x-0,1x²-x²+0,1x=
2,9x²-3,9x
1 1 1
2010-03-15T22:38:23+01:00
A)
(a+b)-(2a-b)-(a-2b) = a+b-2a+b-a+2b = 4b-2a

b)
(3x-y+1)-(x+y)+(y-x) = 3x-y+1-x-y+y-x = x-y+1

c)
-(kx+ny)-(3kx+2ny)+(5kx-3ny) =-kx-ny-3kx-2ny+5kx-3ny = kx-6ny

d)
(2ab+a+3)-(3ab-a+3) = 2ab+a+3-3ab+a-3 = 2a-ab

e)
(4x²-3x)-(x+0,1x²)-(x²-0,1x) = 4x^-3x-x-0,1x^-x^+0,1x = 2,9x^-3,9x
3 2 3